Liver-specific FGFR4 knockdown in mice on an HFD increases bile acid synthesis and improves hepatic steatosis - Francois Moreau; Bruna Brasil Brunao; Xiang-Yu Liu; Frederic Tremblay; Kevin Fitzgerald; Julian Avila-Pacheco; Clary Clish; Ronald C. Kahn; Samir Softic (Journal of Lipid Research, 2023)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease with increased risk in patients with metabolic syndrome. There are no FDA-approved treatments, but FXR agonists have shown promising results in clinical studies for NAFLD management. In addition to FXR, fibroblast growth factor receptor FGFR4 is a key mediator of hepatic bile acid synthesis. Using N-acetylgalactosamine–conjugated siRNA, we knocked down FGFR4 specifically in the liver of mice on chow or high-fat diet and in mouse primary hepatocytes to determine the role of FGFR4 in metabolic processes and hepatic steatosis. Liver-specific FGFR4 silencing increased bile acid production and lowered serum cholesterol. Additionally, we found that high-fat diet–induced liver steatosis and insulin resistance improved following FGFR4 knockdown. These improvements were associated with activation of the FXR-FGF15 axis in intestinal cells, but not in hepatocytes. We conclude that targeting FGFR4 in the liver to activate the intestinal FXR-FGF15 axis may be a promising strategy for the treatment of NAFLD and metabolic dysfunction.